PENERAPAN METODE ROLE PLAYING PADA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Zulfikar Is Paudi (Jurnal Pendidikan Sains Indonesia, 2019)
Research  dealing  with  Role-Play  Learning  and  Conventional  Learning  methods,  have  been conducted.  The  main  reason  for  this  research  was  that  chemical  bond  was  one  of  the  difficult  but fundamental materials to be mastered by the students at grade X. The purpose of this research was to investigate the students’ achievement on the topic of Hukum Newton at SMA Negeri 1 Palu. One way of increasing their achievement was by using Role-Play method. In order to make their learning understandable, not boring, and easy to grasp, the researcher applied an interesting method called Role- Play.  The  population  of  this  research  was  the  tenth  grade  students  of  SMA  Negeri  1  Palu  in the  academic  year  2017/2018.  The  sample  was  32  students  of  grade  XA as  the  experimental  group (Role-Play) and 32 students of grade XC as the control group (Conventional Learning). The data were collected through the test on Hukum Newton. Based on the analysis, it is found that the average score of the experimental group was 20.65 with deviation standard of 2.413 and of the control group was 15.06 with deviation standard of 2.975. The hypothesis testing was that the t-counted value was 12.75 and the t-table value was 1.67 with the significant value (α) of 0.05. The results showed that there was a significant difference in the students’ achievement dealing with the topic of Hukum Newton through the application of Role-Play Learning method and Conventional Learning method at grade X at SMA Negeri 1 Palu in the Academic Year 2017/2018.